PENGARUH ESG DISCLOSURE TERHADAP ROA, LDR, CAR PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA 2023-2024 - Elizach Citra Permatasari; Nurmala Ahmar (Jurnal Ilmiah Akuntansi Pancasila (JIAP), 2026)
The implementation of the addiction principle is now a requirement for the banking sector to maintain public trust and economic stability. This study aims to analyze the influence of Environmental, Social, and Governance (ESG) on financial performance, as proxied by ROA, LDR, and CAR, in banking companies listed on the Indonesia Stock Exchange (IDX) during the 2023-2024 period. The research method uses a quantitative approach with panel data regression analysis and Robust Estimation. Secondary data obtained through purposive sampling of 27 selected banking companies over 2 years were processed using E-Views version 12. The results show that ESG compliance has a significant positive effect on ROA and CAR, but a significant negative effect on LDR. Companies that implement compliance with regulations are not only considered voluntary but also an obligation that has been proven to affect the financial health of banks and their competitiveness in the eyes of stakeholders.